Georgia Architectural and Historic Properties Survey of Colonial Store and Handy Food Store on East Railroad Ave., U.S. 41, Sycamore, Turner County, Ga., 1981 - Barton and Harbin (South Georgia Area Planning and Development Commission, 1981)
Georgia Architectural and Historic Properties Survey of Emile St., Sycamore, Turner County, Ga., 1981. Small double pen house with tin gabled roof. Shed porch surrounded by square posts. Asbestos shingle siding. Double sash windows with 2/2 and 4/4 lights. Brick piers. Poor condition. Date of Construction: c. 1910. Not significant as part of a potential National Register historic district. Area of older structures not extensive enough.
Georgia Architectural and Historic Properties Survey of Colonial Store on East Railroad Ave., U.S. 41, Sycamore, Turner County, Ga., 1981. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 55.8 MB (58,543,723 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Sycamore (Ga.); Turner County (Ga.)